Synthesis and biological evaluation of azetidinone derivatives as antibacterial and Antifungal agents - DARPAN B. PATEL,; VIKAS A. DESAI, (International Journal of Pharma and Bio Sciences, 2017)
We have developed a novel approach for the preparation of N-[(Z)-arylmethylidene] pyrrolidine-2-carboxamide using catalytic acetic acid through the reaction of different substituted benzaldehyde with L-Prolinamide. These molecules were further cyclized with chloroacetylchloride under nucleophilic substitution reaction condition to finally afford 3-chloro-4-aryL-1-[(2S)-pyrrolidin-2-ylcarbonyl]azetidin-2-one. These synthesized compounds were further confirmed by IR, 1H NMR, and mass spectroscopy. All these final synthesized compounds have been screened for their biological activity against different strains for their antibacterial and antifungal activity.